The relationship between brand reliability and behavioral inclinations, concerning the mediation role of perceptual consequences of Brand (Case study: Adidas store in Tehran) - Eskandarpour, Behrouz (Revista de la Universidad del Zulia, 2019)
Concerning the sensitive competitive condition in the world, each store inorder to achieve its superior aims, namely, fundraising and increasingbusiness efficiency alongside all problems and official disciplines(official provisions, note office), needs to possess hardworking,energetic, considerate, and liable personnel for attracting and retainingcustomers. This research was done in Adidas store of Tehran, with thepurpose of investigating the relationship between brand reliability andbehavioral inclinations, concerning the mediation role of perceptualconsequences of Brand. This study is a practical one and data collectionmethod was descriptive and survey based. The statistical communityconsisted of whole customers of Adidas store in Tehran. To examineresearch hypothesis a sample of 400 customers were selected randomly.For data collection regarding literature of research, library method wasused (studying books and articles) and for hypothesis testing standardquestionnaire was used based on 5- point Likert scale. Reliability ofquestionnaire was confirmed by experts and respective professors’ point of view. Reliability coefficient based on Cronbach’s alpha was calculated (0.921). For data analysis, confirmatory factor analysis and structural equation modeling were used. The results of study showed that, brand reliability has a positive impact on customer satisfaction, loyalty and commitment, and continuous commitment of customers. Also, customer satisfaction, loyalty and commitment have a positive impact on inclinations to oral advertising, and it was observed that, when customer satisfaction, loyalty and commitment are high, customers’ tendency for changing store will decrease.